Ethnic disparities in infectious disease hospitalisations in the first year of life in New Zealand. (7th October 2016) - Hobbs, Mark R; Morton, Susan MB; Atatoa-Carr, Polly; Ritchie, Stephen R; Thomas, Mark G; Saraf, Rajneeta; Chelimo, Carol; Harnden, Anthony; Camargo, Carlos A; Grant, Cameron C
Abstract : Aim: Infectious disease (ID) hospitalisation rates are increasing in New Zealand (NZ), especially in pre‐school children, and Māori and Pacific people. We aimed to identify risk factors for ID hospitalisation in infancy within a birth cohort of NZ children, and to identify differences in risk factors between ethnic groups. Methods: We investigated an established cohort of 6846 NZ children, born in 2009–2010, with linkage to a national data set of hospitalisations. We used multivariable logistic regression to obtain odds ratios (OR) for factors associated with ID hospitalisation in the first year of life, firstly for all children, and then separately for Māori or Pacific children. Results: In the whole cohort, factors associated with ID hospitalisation were Māori (OR: 1.49, 95% CI: 1.17–1.89) or Pacific (2.51; 2.00–3.15) versus European maternal ethnicity, male gender (1.32; 1.13–1.55), low birthweight (1.94, 1.39–2.66), exclusive breastfeeding for <4 months (1.22, 1.04–1.43), maternal experience of health‐care racism (1.60, 1.19–2.12), household deprivation (most vs. least deprived quintile of households (1.50, 1.12–2.02)), day‐care attendance (1.43, 1.12–1.81) and maternal smoking (1.55, 1.26–1.91). Factors associated with ID hospitalisation for Māori infants were high household deprivation (2.16, 1.06–5.02) and maternal smoking (1.48, 1.02–2.14); and for Pacific infants were delayed immunisation (1.72, 1.23–2.38), maternal experience of health‐care racism (2.20, 1.29–3.70) and maternal smoking (1.59, 1.10–2.29). Conclusions: Māori and Pacific children in NZ experience a high burden of ID hospitalisation. Some risk factors, for example maternal smoking, are shared, while others are ethnic‐specific. Interventions aimed at preventing ID hospitalisations should address both shared and ethnic‐specific factors.